COMPARISON OF CHLORINATION, ULTRAVIOLET RADIATION AND SOLAR RADIATION (SODIS), IN CONTINUOUS FLOW FOR WASTEWATER DISINFECTION - MOREIRA DA SILVA, MARCELO JACOMINI; STIPP PATERNIANI, JOSÉ EUCLIDES (Revista Brasileira de Engenharia de Biossistemas, 2009)
This research work had the objective to compare chlorination, ultraviolet radiation (UV), and solarradiation (SODIS) efficiency on domestic wastewater disinfection. Chlorination was made using Sodiumhypochlorite, exposition to UV radiation was made using a tubular type reactor with a submerse bulblight and a continuous flow SODIS was constructed at the research institution being a long metallicrectangular channel covered with acrylic transparent plates. The results showed that UV radiationreactor had efficiency values close the ones obtained by chlorination, being an alternative processwith lower risks to form carcinogenic products. The continuous flow SODIS did not reach 50º C duringevaluation period. This indicated that there are necessities to make reactor conception changes toobtain a continuous flow process efficient as batch SODIS process. Problems arising due to growingof algae in the continuous flow SODIS also were observed